PROKINETIC AND LAXATIVE EFFECTS OF XIAO’ER QIXINGCHA, A HOUSEHOLD PEDIATRIC HERBAL FORMULA - Wang, Xiu-Fen; Huang, Xiao-Dan; Zhao, Xiao-Ning; Xie, Jian-Hui; Su, Ji-Yan; Mo, Zhi-Zhun; Su, Zi-Ren; Zhang, Xiao-Jun; Chen, Wei-ping (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Xiao’er Qixingcha, a household Chinese Medicinal formula, has been extensively applied in pediatric clinic for dyspepsia and constipation for hundreds of years. The present study firstly inspected whether the extract of Xiao’er Qixingcha (EXQ) has in vivo and in vitro prokinetic and laxative effects, and evaluated its acute toxicity. Materials and methods: In the in vivo study, small intestinal transit rates and fecal output characters (number and fecal weight) were measured on normal and two models of constipated mice (induced by diphenoxylate and by water-fasting respectively). In the in vivo study, the contraction rates of ileum smooth muscle were examined with EXQ treatment. Moreover, in acute toxicity study, EXQ was administered orally for 14 days to juvenile SD rats, and clinical signs, viscera lesion and body weight were monitored daily. Results: EXQ at all doses significantly increased the small intestinal transit rates, and ameliorated the fecal output characters of normal mice. In diphenoxylate-induced constipated mice, EXQ dose-dependently improved the small intestinal transit rates and fecal output. In water-fasting-induced constipated mice, EXQ dose-dependently improved the small intestinal transit rates, and significantly ameliorated the fecal output characters at 2.92 and 6.75 g/kg. Furthermore, in the in vitro study, EXQ dose-dependently raised the contraction rates of the isolated rabbit ileum smooth muscle. Finally, the acute toxicity study indicated that no toxicological effect was observed in terms of clinical signs, viscera lesion or change of body weight. Conclusions: Taken together, EXQ exhibited prominent prokinetic and laxative activities, promising it as a safe and effective alternative pharmaceutical therapy for constipation.